Seasonal variation of zooplankton community structure and trophic position in the Celtic Sea: A stable isotope and biovolume spectrum approach. (October 2019) - Giering, Sarah L.C.; Wells, Seona R.; Mayers, Kyle M.J.; Schuster, Hanna; Cornwell, Louise; Fileman, Elaine S.; Atkinson, Angus; Cook, Kathryn B.; Preece, Calum; Mayor, Daniel J.
Graphical abstract: Abstract: Zooplankton on continental shelves represent an important intermediary in the transfer of energy and matter from phytoplankton to the wider ecosystem. Their taxonomic composition and trophic interactions with phytoplankton vary in space and time, and interpreting the implications of this constantly evolving landscape remains a major challenge. Here we combine plankton taxonomic data with the analysis of biovolume spectra and stable isotopes to provide insights into the trophic interactions that occur in a shelf sea ecosystem (Celtic Sea) across the spring-summer-autumn transition. Biovolume spectra captured the seasonal development of the zooplankton community well, both in terms of total biomass and trophic positioning, and matched trophic positions estimated by stable isotope analysis. In early April, large microplankton (63–200 µm) occupied higher trophic positions than mesozooplankton (>200 µm), likely reflecting the predominance of nanoplankton (2–20 µm) that were not readily available to mesozooplankton grazers. Biomass and number of trophic levels increased during the spring bloom as elevated primary production allowed for a higher abundance of predatory species. During July, the plankton assemblage occupied relatively high trophic positions, indicating important links to the microbial loop and the recycling of organic matter. The strong correlation between biomass and community trophic level across the study suggests that the Celtic Sea is a relatively enclosed and predominantly energy-limited ecosystem. The progression of the zooplankton biomass and community structure within the central shelf region was different to that at the shelf-break, potentially reflecting increased predatory control of copepods by macrozooplankton and pelagic fishes at the shelf break. We suggest that the combination of size spectra and stable isotope techniques are highly complementary and useful for interpreting the seasonal progression of trophic interactions in the plankton.